Sources of Funds and Specialization Patterns of European Venture Capital Investments - Andrea Schertler (Kiel Institute for World Economics (IfW), 2004)
This paper analyses the link between venture capitalists' sources of funds, such as banks and pension funds, and the specialization pattern of venture capital investments in particular industries and particular stages of enterprises' development. Based on a panel data set of Western European countries, the results of the analysis show that sources of funds and investment specialization patterns are linked. For example, the specialization in the early stage of enterprises' development depends positively on the importance of pension funds and negatively on the importance of banks as sources of funds. These results reject models that assume independence of sources of funds and investment patterns.
Keywords: G32; G24; 330; sources of funds; venture capital; Europe; panel data; Risikokapital; Investmentfonds; Eigentümerstruktur; Kapitalanlage; Branche; Unternehmensentwicklung; Schätzung; Westeuropa